Second-hand? Insights into the age and 'authenticity' of colonial period rock art on the Sunshine Coast, Queensland, Australia. (February 2018) - Huntley, Jillian; George, Steven; Sutton, Mary-Jean; Taҫon, Paul
Abstract: The materials used to create rock art preserve information regarding how and, in some instances, when it was made. Here we outline the field based, geochemical study of three white hand stencils on the Sunshine Coast of Queensland, Australia. Portable X-ray fluorescence analysis determined that all hand stencils were made using a titanium based pigment, almost certainly commercially produced white paint. Significantly this helped us assign a chronology, inferring that the rock art must have been produced in the colonial period. The amount of titanium in the paint likely reflects a mid-twentieth century recipe, specifically > 1960, rather than a modern, twenty first century paint. The manner in which the stencils were made and their arrangement upon the sandstone boulder is consistent with Aboriginal rock art across the continent, and chemical indicators of post-depositional weathering suggest the stencils have been in place for many decades. Rather than 'second-hand copies' of Aboriginal art made by European descendants, we suggest that these stencils provide rare insight into the continuing cultural traditions of the Indigenous peoples of southeast Queensland during the mid-1900s, a time of significant socio-political change for Aboriginal Australians. Graphical abstract: Image 1 Highlights: White pigment used to produce Aboriginal Rock Art reviewed. pXRF analyses determine white hand stencil composition on the Sunshine Coast. Paint chemistry shows Titanium pigments were used to make three hand stencils. The amount of Titanium indicates mid-twentieth century mass-manufactured paint. These 'authentic' stencils offer a rare insight into colonial Rock Art in Australia.